Serotyping Group B Streptococci in a Small Community Hospital: An Analysis of Distribution and Site of Isolation - Jennifer M. Smith; Jason A. Rexroth; David G. Chaffin; Susan H. Jackman (Hindawi Limited, 2002)
Objective: To determine the prevalence and site of isolation of different serotypes of group B streptococcus (GBS) colonization or infection at a small community hospital.